Association between statin use and plasma D-dimer levels - Sahebkar, Amirhossein; Serban, Corina; Mikhailidis, Dimitri P.; Undas, Anetta; Lip, Gregory Y. H.; Muntner, Paul; Bittner, Vera; Ray, Kausik K.; Watts, Gerald F.; Hovingh, G. Kees; Rysz, Jacek; Kastelein, John J. P.; Banach, Maciej; Lipid and Blood Pressure Meta-analysis Collaboration (LBPMC) Group (Thrombosis and Haemostasis, 2015)
D-dimers, specific breakdown fragments of cross-linked fibrin, are generally used as circulating markers of activated coagulation. Statins influence haemostatic factors, but their effect on plasma D-dimer levels is controversial. Therefore, the aim of this meta-analysis was to evaluate the association between statin therapy and plasma D-dimer levels. We searched PubMed, Web of Science, Cochrane Library, Scopus and EMBASE (up to September 25, 2014) to identify randomised controlled trials (RCTs) investigating the impact of statin therapy on plasma D-dimer levels. Two independent reviewers extracted data on study characteristics, methods and outcomes. Meta-analysis of data from nine RCTs with 1,165 participants showed a significant effect of statin therapy in reducing plasma D-dimer levels (standardised mean difference [SMD]: –0.988 µg/ml, 95 % confidence interval [CI]: –1.590 – –0.385, p=0.001). The effect size was robust in sensitivity analysis and omission of no single study significantly changed the overall estimated effect size. In the subgroup analysis, the effect of statins on plasma D-dimer levels was significant only in the subsets of studies with treatment duration ≥ 12 weeks (SMD: –0.761 µg/ml, 95 %CI: –1.163– –0.360; p< 0.001), and for lipophilic statins (atorvastatin and simvastatin) (SMD: –1.364 µg/ml, 95 % CI: –2.202– –0.526; p=0.001). Hydrophilic statins (pravastatin and rosuvastatin) did not significantly reduce plasma D-dimer levels (SMD: –0.237 µg/ml, 95 %CI: –1.140–0.665, p=0.606). This meta-analysis of RCTs suggests a decrease of plasma D-dimer levels after three months of statin therapy, and especially after treatment with lipophilic statins. Well-designed trials are required to validate these results.Note: The review process for this paper was fully handled by Christian Weber, Editor in Chief.
Keywords: D-dimer; statin; coagulation; fibrinolysis